Viability of Urban Residents: Content of the Concept, Theoretical and Empirical Possibilities of Its Application - Drobysheva, Tatiana; Emelyanova, Tatiana (Saratov State University, 2020)
The purpose of the study presented in the article is to theoretically and methodologically substantiate the appropriateness of applying the concept of "viability of urban residents" in the studies of urban social psychology. Interdisciplinary analysis of approaches to the study of the problem of "human being and the city" has been carried out. It is noted that introduction of the concept of "viability of urban residents" into scientific circulation will allow, on the one hand, to study factors and mechanisms of vital resources of different groups of urban residents from a new perspective, and, on the other hand, it will expand the subject area of p sychology of large social groups. The task that we set was to include the category of "viability of city residents" in the existing thesaurus of concepts used in the study of social psychology of the city. It has been shown that the existing directions of research on the perception of the city, social representations of residents, satisfaction with life in the city, approaches through phenomena of identity and values o f residents, viewed from different angles, provided understanding of the variety of psychological factors of urban residents' viability. It has been stated that the problem of accumulating this knowledge by means of introducing a concept which synthesizes various aspects of social psychology of urban residents is becoming urgent. It has been shown that this role can be fulfilled by the concept of residents' viability, which, due to its many aspects, will be useful for studying the potential that provides a productive and proactive start in the life of large social groups of urban residents (age-related, ethnic, religious, professional, etc.). Such components of the viability of large groups of urban residents as cognitive, value-affective, and motivational-volitional components have been distinguished. The content of each of these components has been discussed and ways of their empirical research have been proposed when comparing viability of urban residents with different economic, geographical, environmental and cultural characteristics.